TRANSFORMATIONAL LEADERSHIP OF THE PRINCIPAL IN PROMOTING DEEP LEARNING IMPLEMENTATION: A QUALITATIVE CASE STUDY AT MUARA TIGA PUBLIC JUNIOR HIGH SCHOOL 2 - Iswadi Iswadi; Harlinda Syofyan; Mujazi Mujazi; Sarlina Sari (Institut Agama Islam Al Hidayah Bogor, 2026)
Implementing deep learning requires pedagogical shifts, teacher readiness, and organizational support, particularly in rural schools facing limited access to educational innovations and resources. This study aims to explore how the principal's transformational leadership supports the implementation of deep learning at SMP Negeri 2 Muara Tiga. A qualitative approach with a single-case study design was employed. Data were gathered from eight informants using interviews, observations, and document analysis. The data analysis process followed a structured sequence: data reduction and coding, data display, and conclusion drawing. Data validity was ensured through triangulation. The findings indicate that transformational leadership supports deep learning implementation through four key dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These practices were reinforced by teacher competency development, collaborative planning, organizational flexibility, and a dialogic approach to addressing resistance. The findings also reveal that these practices fostered a more adaptive, collaborative, and reflective deep learning implementation process at SMP Negeri 2 Muara Tiga. The study concludes that transformational leadership serves as a mechanism for managing pedagogical change and supporting teacher readiness for deep learning implementation within a rural school context.